3*(2x-1)=4x-9

Simple and best practice solution for 3*(2x-1)=4x-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3*(2x-1)=4x-9 equation:


Simplifying
3(2x + -1) = 4x + -9

Reorder the terms:
3(-1 + 2x) = 4x + -9
(-1 * 3 + 2x * 3) = 4x + -9
(-3 + 6x) = 4x + -9

Reorder the terms:
-3 + 6x = -9 + 4x

Solving
-3 + 6x = -9 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-3 + 6x + -4x = -9 + 4x + -4x

Combine like terms: 6x + -4x = 2x
-3 + 2x = -9 + 4x + -4x

Combine like terms: 4x + -4x = 0
-3 + 2x = -9 + 0
-3 + 2x = -9

Add '3' to each side of the equation.
-3 + 3 + 2x = -9 + 3

Combine like terms: -3 + 3 = 0
0 + 2x = -9 + 3
2x = -9 + 3

Combine like terms: -9 + 3 = -6
2x = -6

Divide each side by '2'.
x = -3

Simplifying
x = -3

See similar equations:

| -9+2u=u | | x-4/7=1/3 | | 20x+12=92 | | 2.67=(x/100)*2 | | 21763=974x+15910 | | 4+x^2= | | -22n-2=65 | | 2b=b+6 | | 2(9x+9)=6(3x+3) | | 2x+7+x-6=100 | | 2x+1=5x-35 | | 10+v=-4v | | c=2*3.16*r | | 7x-5y+4=0 | | 4h-3+9=22 | | 2x=4028 | | 8n-2-8= | | 3/5x-9=6 | | 3+8z+z^2=0 | | 2(7v+1)=-14-2v | | .5/y=.02 | | 19=0.5x+5 | | (2x+1)=4(x-3) | | 32+5r=-8(-1-r) | | 17g-16g+1=14 | | 7x+1-4x=4x-5+1 | | 2(-5/2)^2-(-5/2)-15 | | 6x+4y=3x-8 | | j-13=46 | | 3y*2+5*2=5y*3 | | 34x+3=45 | | P+.15p=23 |

Equations solver categories